Analisis Learning Obstacle Siswa Madrasah Tsanawiyah dalam Materi Aljabar - Meika, Ika; Mulyanah, Mulyanah; Sartika, Nenden Suciyati; Sujana, Asep (MENDIDIK: Jurnal Kajian Pendidikan dan Pengajaran, 2024)
Education is one of the main pillars in building a country's civilization, which aims to develop the potential of students optimally. Mathematics, especially algebra, plays an important role in the development of science and technology. This research aims to identify learning obstacles experienced by students in solving algebra problems. The research method is descriptive with a qualitative approach which was carried out on March 5 2024 on 27 class VIII students at MTs Mathla'ul Anwar Baros. The instrument used is a learning obstacle test which has been validated by experts. The results of the analysis show that the majority of students experience difficulty in working on algebra problems, with 61% having difficulty in concepts, 65% of students having difficulty in carrying out arithmetic operations and 43% of students having difficulty in procedures. The learning obstacles that cause errors in answering the test questions are that students do not understand the concept of solving algebra material well, students do not understand the meaning of variables, students still rely on rote methods to remember formulas, resulting in difficulties in algebraic operations that do not use certain formulas, and students' inaccuracy in working on questions.